Identifikasi Pengembangan Digital Supply Chain pada Industri Pengolahan Sampah - Yohanes Anton Nugroho (Pusat Riset dan Inovasi Nasional, 2022)
Technology developments in the era of the industrial revolution 4.0 provide many opportunities to improve supply chain performance and performance. The existence of the waste processing industry as a business has prospects for development, given the large amount of waste generated by the community and the need for several processed products. PT A reduced the amount of garbage that accumulates in the final disposal site (TPA) by reprocessing the waste produced by the community. The existence of waste banks, government agencies, hotels, zoos, and Islamic boarding schools is one of the sources of waste that is processed for waste products. This paper seeks to develop the concept of a digital supply chain by adopting the supply chain model run by PT A. The initial identification presented in this paper can result in several technology identifications that need to be prioritized in implementing relevant technologies in the industry. The expected impact of this implementation is an increase in supply chain performance